Simultaneous complementary photoswitching of hemithioindigo tweezers for dynamic guest relocalization - Wiedbrauk, Sandra; Bartelmann, Thomas; Thumser, Stefan; Mayer, Peter; Dube, Henry (Nature Communications, 2018)
Remote control of complex molecular behavior and function is one key problem in modern chemistry. Using light signaling for this purpose has many advantages, however the integration of different photo processes into a wholesome yet complex system is highly challenging. Here we report an alternative approach to increase complexity of light control-simultaneous complementary photoswitching-in which spectral overlap is used as an advantage to drastically reduce the signaling needed for controlling multipart supramolecular assemblies. Two photoswitchable molecular tweezers respond to the same light signals with opposite changes in their binding affinities. In this way the configuration of two host tweezers and ultimately the dynamic relocation of a guest molecule can be trigged by only one signal reversibly in the same solution. This approach should provide a powerful tool for the construction of sophisticated, integrated, and multi-responsive smart molecular systems in any application driven field of chemistry.
CRIS-Team Scopus Importer:2020-04-02